2019
DOI: 10.1039/c8ra09785b
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state AIEnh-circularly polarised luminescence of chiral perylene diimide fluorophores

Abstract: Chiral N,N′-bis(1-phenylethyl)perylene-3,4,9,10-tetracarboxylic acid diimide (BPP) exhibits solid-state aggregation-induced enhanced circularly polarized luminescence (AIEnh-CPL) in KBr, PMMA, and myo-IPU matrices..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 54 publications
0
33
0
Order By: Relevance
“…This also suggests that it is possible to control the CPL properties by changing the environment of the chiral compound without using an enantiomer. Taniguchi et al (2019) reported the observation of aggregation-induced enhanced (AIEnh) CPL of chiral perylene diimide fluorophores in a KBr pellet, a PMMA film and a myo-IPU-film. Louis et al (2019) reported mechano-responsive CPL by thermal annealing and smearing of a solid-state sample.…”
Section: Introductionmentioning
confidence: 99%
“…This also suggests that it is possible to control the CPL properties by changing the environment of the chiral compound without using an enantiomer. Taniguchi et al (2019) reported the observation of aggregation-induced enhanced (AIEnh) CPL of chiral perylene diimide fluorophores in a KBr pellet, a PMMA film and a myo-IPU-film. Louis et al (2019) reported mechano-responsive CPL by thermal annealing and smearing of a solid-state sample.…”
Section: Introductionmentioning
confidence: 99%
“… Ultraviolet‐visible (UV‐vis) absorption spectral (dotted lines) and photoluminescence (PL) (solid lines) profiles recorded for ( R , R )‐ BPP (black lines), [36] ( R , R )‐ Ethy (green lines), ( R , R )‐ BPP‐Ph (blue lines), and ( R , R )‐ BPP‐EthyPh (red lines) in their (a) CHCl 3 solution (1.0×10 −4 M) and (b) PMMA‐film states. λ ex =450 nm for ( R , R )‐ BPP , 470 nm for ( R , R )‐ Ethy , 456 nm for ( R , R )‐ BPP‐Ph , and 456 nm for ( R , R )‐ EthyPh .…”
Section: Resultsmentioning
confidence: 99%
“… Circular dichroism (CD) spectral profiles recorded for ( R , R )‐ BPP (black lines), [36] ( R , R )‐ Ethy (green lines), ( R , R )‐ BPP‐Ph (blue lines), and ( R , R )‐ BPP‐EthyPh (red lines) in their (a) CHCl 3 solution (1.0×10 −4 M) and (b) PMMA‐film states.…”
Section: Resultsmentioning
confidence: 99%
“…[11,12,15] Notably, the absolute PLQY of CNC-QNR-PU films was observed to be 6.5%, which is an order of magnitude higher than that of other polymer-based emissive chiro-optical films. [62][63][64] Remarkably, when the films were stretched, they showed no asymmetric CPL emission, yet linearly polarized light emission parallel to the stretching direction was observed (Figure 4c; Figure S20, Supporting Information).…”
Section: Mechanically-triggered Dynamic Light Polarizationmentioning
confidence: 99%